Mistura de sais microparticulados: uma alternativa para redução de sódio em batata palha - Rodrigues, Daniela Maria (2015)
Excess in sodium intake is the main cause of cardiovascular diseases, especially hypertension, a major health problem worldwide. Although several factors influences the sodium intake by the population, processed food are the main source of this mineral. Thus, several strategies have been adopted in order to reduce the salt content of such products. On the other hand, to please the consumer and maintain your preferences, reduction in sodium content without affecting the organoleptic quality of the product is a challenge. This study aimed to combine two strategies to reduce sodium content: the use of substitutes and reduction of the salt particles, aiming to further reduce the sodium content. Thus, the objective was to determine the equivalence and salting potency of salts mixture (sodium chloride, potassium chloride, and monosodium glutamate) with reduced particles sizes of these salts in shoestring potatoes. The magnitude scale method was used to find the salting equivalence of the salts mixture of reduced particle size (90% of which were smaller than 193.4; 117.07; 88.18 e 59.6 µm, respectively based on the ideal salt value (1.6% of sodium chloride) which should be added to the shoestring potatoes at concentrations of 0.93; 0.85; 0.83 e 0.79% respectively. Then, a temporal dominance of sensations analysis was performed to evaluate the sensory profile of these salts mixtures in shoestring potatoes, followed by the time-intensity analysis to assess the intensity of salty taste. The salts mixture with particles size of 117.07 µm was considered the one, which achieved the purposes of this study, without changing the sensory characteristics of the product and reducing 68.75% sodium. Thus, it can be considered a viable alternative for reducing sodium in shoestring potatoes.